Cultural inclusion in outdoor spaces: a cultural inquiry of Chester I. Lewis Reflection Square Park in Wichita, Kansas - Lemken, Andrea (Kansas State University, 2018)
Chester I. Lewis Reflection Square Park in Downtown Wichita, Kansas commemorates the life of Chester I. Lewis, president of the Wichita Chapter of the National Association for the Advancement of Colored People (NAACP) in 1958 and leader of the Dockum Drugstore Sit-In of 1958, the first successful sit-in of the Civil Rights Movement in the United States. In its current condition, the reflection park is underutilized and often subject to vandalism. As a historically significant park, it is important to the community of Wichita to maintain the integrity of the meaning of the site while simultaneously improving the physical design. The purpose of this project is to provide a redesign of the historically significant Chester I. Lewis Reflection Square Park which reflects the implication of the reflection park as a culturally inclusive and historically significant downtown space. Access to culturally and socially inclusive outdoor spaces is imperative to providing opportunity for people of all different backgrounds to personally connect to the space. While the goal of this project is to design inclusive spaces, the author recognizes inclusiveness in a space is interpreted by and culturally dependent on the user of the space (Kemmis, S., & McTaggart, R. 2000). The author conducted research through a cyclical process of engagement meetings with stakeholders, one-on-one interviews with Wichita community members, and design proposals for Lewis Park. Content analysis was performed on data from meetings and interviews to inform a set of guidelines to redesign Lewis Park. Theories of cultural interpretation were also explored to recognize how to integrate different audiences into one culturally inclusive outdoor space (Ulrich 1986). Findings include guidelines guided by community input for designing Lewis Park as a culturally inclusive outdoor space and a theoretical design proposal for stakeholders and the City of Wichita to consider. The redesign of the reflection park was driven by the aspiration to reflect the cultures of Wichita’s ethnically and racially diverse communities in the contemporary context of dialogue on race and memorials in public space.
Keywords: Cultural inquiry; Cultural inclusion; Recursive design; Commemoration; Cultural garden identities; Participatory design